Шотландская эмиграционная поэзия США середины XIX в. : сюжеты и символы - Велилаева, Л.Р. (Культура народов Причерноморья, 2014)
В данной статье рассмотрены основные соцтокультурные явления Шотландии и США XIX
века с позиции символики «своего-чужого (другого)». Определены основные критерии данного
соотношения, тематика и сюжетика поэтических текстов Х. Эйнсли, Д.К. МакКаллума и В. Вильсона. В поданій статті розглянуті головні соціокультурні явища Шотландії та США XIX століття з
позицій символіки «свого-чужого (іншого)». Окреслені основні критерії цього співвідношення, тематика і
сюжетика поетичних текстів Х. Ейнслі, Д.К. МакКаллума і В. Вільсона. The paper deals with the main historical events of the nineteenth century Scotland and the USA and their
link with the development of Scottish emigratory poetry. Scotland’s history of the mentioned period is marked with
industrialization, urbanization and population increase on the one hand and with slow town building, deficiency in
medical service, food; Highland Clearance and as a result the decline of Scottish clan system on the other hand.
The USA’s nineteenth century history is described by such facts: armed conflict with the United Kingdom, «South
emigration» from the USA, declaration of Texas’ independence, the Abolitionism movement, Civil War (1861-
1865) and the abolition (1865).
All these historical facts are analysed in the context of Scottish emigratory poetry represented by works of
H. Ainslie, D.C. MacCallum and W. Wilson. Language, ethnic and religious criteria are taken into account in
«one’s own – strange (another’s)» symbolics opposition study. Core symbolics for H. Ainslie’s, D.C. MacCallum’s
and W. Wilson’s poems is «own Scottish» (in the meaning of «one’s own») symbolics (according to the usage of
Scottish historical facts and people, Scots as a poetic language and the attitude to Scotland and the USA). As for
«strange (another’s)» symbolics it should be said that new events, heroes and history are rather taken as «strange
but Scottish», «another but Scottish» (or very close to it) than purely «strange» or «another».